High prevalence of integrase mutation L74I in West African HIV-1 subtypes prior to integrase inhibitor treatment. (27th February 2020) - El Bouzidi, Kate; Kemp, Steven A; Datir, Rawlings P; Murtala-Ibrahim, Fati; Aliyu, Ahmad; Kwaghe, Vivian; Frampton, Dan; Roy, Sunando; Breuer, Judith; Sabin, Caroline A; Ogbanufe, Obinna; Charurat, Man E; et al.
Abstract: Objectives: HIV-1 integrase inhibitors are recommended as first-line therapy by WHO, though efficacy and resistance data for non-B subtypes are limited. Two recent trials have identified the integrase L74I mutation to be associated with integrase inhibitor treatment failure in HIV-1 non-B subtypes. We sought to define the prevalence of integrase resistance mutations, including L74I, in West Africa. Methods: We studied a Nigerian cohort of recipients prior to and during receipt of second-line PI-based therapy, who were integrase inhibitor-naive. Illumina next-generation sequencing with target enrichment was used on stored plasma samples. Drug resistance was interpreted using the Stanford Resistance Database and the IAS-USA 2019 mutation lists. Results: Of 115 individuals, 59.1% harboured CRF02_AG HIV-1 and 40.9% harboured subtype G HIV-1. Four participants had major IAS-USA integrase resistance-associated mutations detected at low levels (2%–5% frequency). Two had Q148K minority variants and two had R263K (one of whom also had L74I). L74I was detected in plasma samples at over 2% frequency in 40% (46/115). Twelve (26.1%) had low-level minority variants of between 2% and 20% of the viral population sampled. The remaining 34 (73.9%) had L74I present at >20% frequency. L74I was more common among those with subtype G infection (55.3%, 26/47) than those with CRF02_AG infection (29.4%, 20/68) ( P =  0.005). Conclusions: HIV-1 subtypes circulating in West Africa appear to have very low prevalence of major integrase mutations, but significant prevalence of L74I. A combination of in vitro and clinical studies is warranted to understand the potential implications.